Five-Month-Old Infants Have General Knowledge of How Nonsolid Substances Behave and Interact. (February 2016) - Hespos, Susan J.; Ferry, Alissa L.; Anderson, Erin M.; Hollenbeck, Emily N.; Rips, Lance J.
Experience puts people in touch with nonsolid substances, such as water, blood, and milk, which are crucial to survival. People must be able to understand the behavior of these substances and to differentiate their properties from those of solid objects. We investigated whether infants represent nonsolid substances as a conceptual category distinct from solid objects on the basis of differences in cohesiveness. Experiment 1 established that infants can distinguish water from a perceptually matched solid and can correctly predict whether the item will pass through or be trapped by a grid. Experiments 2 and 3 showed that infants extend this knowledge to less familiar granular substances. These experiments indicate that concepts of cohesive and noncohesive material appear early in development, apply across several types of nonsolid substances, and may serve as the basis of later knowledge of physical phases.